The Optimization of Environmental Policy to Achieve Sustainable Development Goals - Najicha, Fatma Ulfatun; Setia Wijaksana, Muhamad Mahrus; Wulandari, Nurita (Lembaga Contrarius Indonesia, 2023)
In fact, environmental issues have a high complexity. With the existing scope, it seems that the juridical instrument for enforcing environmental issues, namely environmental law, becomes an urgency in order to realize environmental integrity for sustainable development. These legal arrangements are needed to regulate environmental management so that the community has a legal basis that is used as a guide in environmental management based on sustainable development. If you look at the existing reality related to environmental law instruments, the existing regulations on environmental law are prepared by following the needs of environmental protection and integrity. The research method used in this research is normative-juridical which is done by examining library materials or only secondary materials. In relation to the problems presented, it leads to the conclusion that the regulation of environmental law itself has experienced quite a significant development. However, with this significant development, there are still various problematic environmental issues which make the validation of environmental law instruments, which instruments are still weak in enforcement so that they have not been able to provide implications for efforts to fully achieve the predicted sustainable development goals